Tetanus – A Rare But Real Threat. (2018) - Moynan, David; O'Riordan, Ruth; O'Connor, Roisin; Merry, Concepta
Abstract: Tetanus is a potentially fatal disease of the nervous system arising from toxins produced by Clostridium tetani, an anaerobic bacterium found in soil [1 ]. Characterized by muscular rigidity, spasms and autonomic dysregulation its identification and, importantly, its prevention remain critical to the welfare of at risk patients. We present the case of a twenty two year old woman who presented to hospital with trismus and generalized muscle spasms three days following a dog bite to the right hand. Here, we discuss the presentation of generalized tetanus and the use of neurophysiology to facilitate its diagnosis.